Preparation method of GDC barrier layer, electrolyte and solid oxide battery
The method of preparing GDC nanopowder through pyrolysis and using Gd(NO3)3·6H2O and Ce(NO3)3·6H2O as sintering aids in a controlled cold sintering process addresses the challenges of inconsistent shrinkage and impurity introduction, resulting in a high-density GDC barrier layer that improves the performance and stability of solid oxide fuel cells.
Patent Information
- Application Number
- CN202411338864.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
The preparation of thin GDC barrier layers for solid oxide fuel cells faces challenges such as inconsistent shrinkage with the electrolyte material during cold sintering, leading to defects like holes and cracks, and the selection of sintering aids often introduces impurities or requires high annealing temperatures, affecting the performance and density of the barrier layer.
A method involving the preparation of GDC nanopowder through pyrolysis, using Gd(NO3)3·6H2O and Ce(NO3)3·6H2O as sintering aids, and a cold sintering process with controlled pressure and temperature to ensure consistent shrinkage and improve density, reducing the need for high annealing temperatures.
The method results in a high-density GDC barrier layer with improved interface performance, enhancing the stability and performance of solid oxide fuel cells by ensuring uniform particle arrangement and minimizing defects.
Smart Images

Figure CN119208685A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid oxide fuel cells, and in particular relates to a preparation method of a GDC barrier layer, an electrolyte and a solid oxide battery. Background Art
[0002] Solid oxide fuel cells (SOFCs) are considered to be an ideal choice for future energy generation due to their high energy conversion efficiency, low gas emissions and no chemical pollution. Fuel cells are usually composed of a cathode, an anode and an electrolyte. At the anode end, the fuel is decomposed into negative ions and positive ions; the negative ions (electrons) generated by the oxidation of the fuel at the anode are reduced to oxygen at the cathode, completing the external circuit. In addition, there is a barrier layer in solid oxide fuel cells. The barrier layer is located between the electrolyte and the electrode. Its main function is to form a physical and chemical barrier between the electrolyte and the electrode, reducing the direct contact between them, thereby reducing the mutual diffusion and reaction at the interface and avoiding the formation of an insulating phase, which is crucial to maintaining the long-term stable operation of the battery.
[0003] For example, the commonly used electrolyte material YSZ (yttria-stabilized zirconia) has high ionic conductivity, low electronic conductivity, good stability, and good compatibility with other materials. Common cathode materials include La 0.8 Sr 0.2 MnO3(LSM), La 0.6 Sr 0.4 CoO3(LSC), La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3 (LSCM), etc. However, the YSZ electrolyte material easily reacts with Sr and La in the cathode material to form SrZrO3 and LaZrO3, which increases the impedance of the battery and reduces the electrochemical performance. In order to solve this problem, GDC (gadolinium-doped cerium oxide, Ce) is usually added between the electrolyte and the cathode material. 1-x G x O 1-0.5x ) barrier layer, because the GDC material has high ionic conductivity and good chemical stability, and has high chemical compatibility with the electrolyte and cathode materials. The GDC barrier layer can also be used between the electrolyte and the anode to prevent reactions between the electrolyte material and the anode.
[0004] However, GDC ceramics have the problem of poor sintering activity and generally require very high sintering temperatures to be dense. The sintering performance of ceramics depends largely on the microstructural characteristics of the powder, including the shape, size, pore volume and number of grain boundaries of the particles. Reducing the particle size of the powder and adding sintering aids are two commonly used methods to improve the densification performance of ceramics. Ultrafine gadolinium-doped cerium oxide powders can be synthesized by physical or chemical methods to reduce the sintering temperature of GDC, but the commonly used preparation methods are relatively complicated. The sintering temperature can also be reduced by using sintering aids. Currently, commonly used sintering aids include NiO, CuO, CoO, Bi2O3, ZnO, etc. However, the addition of most sintering aids is harmful to the conductive properties of ceramics.
[0005] Cold sintering process (CSP) is a new sintering process developed in recent years. This method helps the powder to densify by adding an intermediate liquid phase and applying external pressure to obtain high-density ceramics. However, this sintering process is currently only used to prepare bulk materials. Compared with bulk materials, the preparation of thin barrier layers requires higher cold sintering technology. Specifically, since the barrier layer material is often coated on the electrolyte material and then sintered with the electrolyte material, the electrolyte material and the barrier layer material may shrink inconsistently, affecting the densification of the barrier layer, and then affecting the performance of the barrier layer. In addition, the barrier layer is usually much thinner than the bulk material, and its sintering driving force is small, and the degree of densification will also be affected, which makes the barrier layer prone to defects such as holes and cracks during the sintering process. In addition, during the sintering process, chemical reactions may also occur at the interface, resulting in deterioration of the interface performance. At the same time, due to the lattice mismatch and thermal stress at the interface, the barrier layer is prone to cracking or peeling during the sintering process. Therefore, compared with bulk cold sintering, barrier layer cold sintering needs to consider more factors and be regulated.
[0006] In addition, the selection of sintering aids is also an important issue in the cold sintering process. In the existing studies on cold sintering of bulk materials, a variety of sintering aids have been used in the preparation of GDC ceramics. Some studies have added deionized water as a sintering aid, but the subsequent annealing temperature required is as high as 1400°C; in order to further reduce the annealing temperature, some studies have used HNO3 / H2O2 mixtures as sintering aids to prepare GDC, but the density of the bulk is relatively low; in addition, some studies have used molten hydroxide as a sintering aid to prepare dense GDC. Although dense bulk can be obtained at a lower temperature, the K in the molten hydroxide + and Na + It will affect the purity of the sample.
[0007] Therefore, how to prepare thin barrier layer materials with stable performance and high density through cold sintering process, and how to reasonably select sintering aids are problems that need to be solved urgently. Summary of the invention
[0008] In order to solve the above technical problems, the embodiment of the present invention discloses a method for preparing a GDC barrier layer of a solid oxide fuel cell, which is characterized by comprising the following steps:
[0009] Preparation of GDC nanopowder: Gd(NO3)3·6H2O and Ce(NO3)3·6H2O were mixed and ground, and then GDC nanopowder was prepared by pyrolysis reaction;
[0010] Preparation of printing powder: GDC nano powder and sintering aid are mixed and ground to obtain printing powder, the sintering aid comprises Gd(NO3)3·6H2O and Ce(NO3)3·6H2O, the molar ratio of Gd(NO3)3·6H2O to Ce(NO3)3·6H2O in the sintering aid is 1:4, and the mass of the sintering aid accounts for 5wt% to 20wt% of the total mass of the sintering aid and GDC nano powder;
[0011] Preparing printing paste: mixing printing powder with a binder to prepare printing paste;
[0012] Cold sintering treatment is performed after screen printing: the printing paste is printed on the electrolyte matrix using a screen plate and dried, and then cold sintering treatment is performed to obtain an initial green body;
[0013] Annealing treatment: The initial green body is annealed to obtain a GDC barrier layer attached to the electrolyte matrix.
[0014] By adopting the above technical scheme, GDC nanopowder with smaller particle size can be obtained through pyrolysis reaction. The smaller particle size is conducive to the densification of the barrier layer. At the same time, Gd(NO3)3·6H2O and Ce(NO3)3·6H2O are selected as sintering aids, which can improve the density, reduce the annealing temperature, and will not volatilize to cause the existence of pores. Combined with the characteristics of cold sintering technology that promotes the close arrangement of GDC nanoparticles through sintering aids and pressure, the consistent shrinkage of the GDC barrier layer and the electrolyte matrix is ensured, and a GDC barrier layer with high density and complete structure can be obtained, thereby improving the interface performance between the GDC barrier layer and the electrolyte matrix, and improving the performance of solid oxide fuel cells.
[0015] Optionally, in the step of preparing GDC nanopowder, a pyrolysis reaction is carried out in a muffle furnace to prepare GDC nanopowder, the heating rate of the pyrolysis reaction is 3-4°C / min, the pyrolysis temperature is 300-400°C, the insulation time is 4-6 hours, and the powder is cooled with the furnace after the insulation is completed.
[0016] Optionally, the GDC nanopowder is Ce 0.8 G 0.2 O 1.9Nano powder, the steps of preparing GDC nano powder include: according to Ce 0.8 G 0.2 O 1.9 Chemical formula Weigh Gd(NO3)3·6H2O and Ce(NO3)3·6H2O, mix and grind.
[0017] Optionally, the mass ratio of the printing powder to the binder is 0.8-1.5, and the binder is prepared by mixing ethyl cellulose and diethyl ethyl acetate in a mass ratio of 3%-10%.
[0018] Optionally, in the cold sintering step after the screen printing, the mesh size of the screen is 200-300 meshes, n layers are printed on the electrolyte matrix, wherein 1≤n≤5, the total thickness of the n layers is 5-20 μm, and the drying temperature is 100-150°C.
[0019] Optionally, the cold sintering temperature of the cold sintering treatment is 250-350° C., the heating rate is 5-20° C. / min, the pressure of the cold sintering process is 150-400 MPa, and the holding time is 0.5-5 hours.
[0020] Optionally, in the cold sintering step after the screen printing, the electrolyte matrix printed with the printing slurry is placed in a mold, a mica sheet is used as a gasket, and a cold sintering treatment is performed, followed by demoulding.
[0021] Optionally, in the annealing step, the annealing temperature is 900-1300° C., the heating rate is 1-10° C. / min, and the holding time is 1-5 hours.
[0022] Optionally, the particle size of the GDC nanopowder is 7 to 15 nm.
[0023] Optionally, the electrolyte matrix is a YSZ electrolyte matrix.
[0024] According to another specific embodiment of the present invention, an embodiment of the present invention discloses an electrolyte for a solid oxide battery, the electrolyte comprising an electrolyte matrix and a GDC barrier layer attached to the electrolyte matrix, and the GDC barrier layer is prepared by the above method.
[0025] By adopting the above technical solution, an electrolyte matrix with high stability in structure and performance can be obtained, which is beneficial to improving the performance of the battery.
[0026] According to another specific embodiment of the present invention, an embodiment of the present invention discloses a solid oxide battery, which includes the above-mentioned electrolyte.
[0027] By adopting the above technical solution, the performance of the battery is improved and the cycle life is extended. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The TEM image of the GDC nanopowder prepared by the pyrolysis method in Example 1 of the present invention is shown;
[0029] Figure 2 shows the XRD pattern of the GDC barrier layer attached to the YSZ electrolyte in Example 1 of the present invention;
[0030] Figure 3 A cross-sectional SEM image of a GDC barrier layer attached to a YSZ electrolyte in Example 1 of the present invention is shown;
[0031] Figure 4 A cross-sectional SEM image of a GDC barrier layer attached to a YSZ electrolyte in Comparative Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0032] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0033] It should be noted that in this specification, similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.
[0034] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0035] The first aspect of the present invention discloses a method for preparing a GDC barrier layer of a solid oxide fuel cell, comprising the following steps:
[0036] Preparation of GDC nanopowder: Gd(NO3)3·6H2O and Ce(NO3)3·6H2O were mixed and ground, and then GDC nanopowder was prepared by pyrolysis reaction;
[0037] Preparation of printing powder: GDC nanopowder and sintering aid are mixed and ground to obtain printing powder, wherein the sintering aid is composed of Gd(NO3)3·6H2O and Ce(NO3)3·6H2O;
[0038] Preparing printing paste: mixing printing powder with a binder to prepare printing paste;
[0039] Cold sintering treatment is performed after screen printing: the printing paste is printed on the electrolyte matrix using a screen plate and dried, and then cold sintered to obtain an initial green body;
[0040] Annealing treatment: The initial green body is annealed to obtain a GDC barrier layer attached to the electrolyte matrix.
[0041] The inventors found through experiments that preparing GDC nano powder by pyrolysis reaction can reduce the particle size of GDC nano powder and improve sintering activity, and compared with sol-gel method, ball milling method and coprecipitation method, pyrolysis method is simpler. Traditional sol-gel method, ball milling method and coprecipitation method pay more attention to the distribution uniformity of particle size, while the present invention pays more attention to the size of particle size, and with the help of pyrolysis reaction, GDC nano powder with small particle size can be prepared. GDC nano powder with small particle size can help improve the density of GDC barrier layer obtained by cold sintering and reduce interface impedance. At the same time, the cold sintering method is adopted, and pressure is assisted in the cold sintering process, which can effectively promote particle rearrangement, improve the density of cold sintered body, make the interface bonding force between sample and electrolyte after cold sintering auxiliary sintering larger, and barrier layer is not easy to fall off.
[0042] If the pyrolysis reaction conditions are further controlled, such as pyrolysis temperature and time, the particle size of the GDC nanopowder can be further reduced.
[0043] In addition, the selection of sintering aids in cold sintering is also very critical. In existing studies, the selection of sintering aids includes deionized water, HNO3 / H2O2 mixtures, and molten hydroxides. These aids have various problems, such as requiring a higher annealing temperature, leaving more pores after the sintering aids volatilize to affect the density, and introducing new impurities. These problems will affect the density and structure of the barrier layer, and thus affect the performance of the battery. In addition, the existing cold sintering sintering aid research is all aimed at GDC bulk materials. The barrier layer has a thinner structure with a thickness of only micrometers, and the matching degree of the barrier layer and the electrolyte matrix needs to be considered. The preparation is more difficult. If the sintering aids of the block are simply applied to the preparation of the barrier layer, it will also bring more problems. During the research and development process, the inventor creatively used the raw materials Gd(NO3)3·6H2O and Ce(NO3)3·6H2O for preparing GDC nanopowders as sintering aids at the same time. It was found that the use of this sintering aid can reduce the subsequent annealing temperature, improve the density of the barrier layer, and will not introduce new impurities. The reason is that the temperature in the first half of the cold sintering process is still relatively low, below 300°C, and Gd(NO3)3·6H2O and Ce(NO3)3·6H2O first become liquid. At this time, the liquid sintering aid plays a lubricating role, which can promote the close arrangement of GDC nanoparticles under pressure. In the later stage of cold sintering, the temperature can be raised to about 300°C, at which time the sintering aid will undergo a pyrolysis reaction and generate GDC particles in situ. These particles can further fill the pores between the original GDC particles, improve the density of the cold-sintered body without introducing new impurities. At the same time, since Gd(NO3)3·6H2O and Ce(NO3)3·6H2O are liquids in the early stage, they have good fluidity and can flow to various parts of the powder material. Therefore, subsequent pyrolysis and particle generation will also occur in various parts, which improves the density of various parts of the GDC barrier layer and makes the structure more uniform. Moreover, since the early pyrolysis reaction generates GDC nanopowder particles with smaller particle size, in the later cold sintering process, it can better combine with the GDC nanopowder particles generated by the pyrolysis of Gd(NO3)3·6H2O and Ce(NO3)3·6H2O sintering aids, which is something that large-sized GDC nanopowder particles cannot do.In addition, if the sintering aids do not use Gd(NO3)3·6H2O and Ce(NO3)3·6H2O, the cold sintering stage is just to pressurize the GDC nano powder itself and perform self-stack extrusion. However, the present invention uses Gd(NO3)3·6H2O and Ce(NO3)3·6H2O as sintering aids, which is to co-press the GDC nano powder and liquid Gd(NO3)3·6H2O and Ce(NO3)3·6H2O. Under the action of pressure, not only the liquid Gd(NO3)3·6H2O and Ce(NO3)3·6H2O are closely attached to the GDC nano powder, but also the original GDC nano powder and the newly generated GDC particles can be more closely combined in the subsequent in-situ growth stage. Therefore, the structure and performance of the GDC barrier layer are more reliable.
[0044] Through the coordination and action of pyrolysis reaction and cold sintering process, the density of the GDC barrier layer can be significantly improved.
[0045] Since the density has been improved during the cold sintering process, the subsequent annealing step does not require such a high annealing temperature to make the GDC barrier layer denser. Furthermore, due to the lower annealing temperature, the barrier layer and the electrolyte body can be calcined at the same temperature as the anode material, simplifying the battery preparation process.
[0046] The above method can conveniently obtain a high-density GDC barrier layer, which helps to improve the performance of solid oxide fuel cells.
[0047] In a specific embodiment of the present invention, in the step of preparing GDC nano powder, a pyrolysis reaction is carried out in a muffle furnace to prepare GDC nano powder, the heating rate of the pyrolysis reaction is 3-4°C / min, the pyrolysis temperature is 300-400°C, for example, 300 degrees Celsius, the holding time is 4-6 hours, for example, 5 hours, and the furnace is cooled after the holding is completed. By regulating the heating rate, pyrolysis temperature, and holding time, it can help to prepare small-sized GDC nano powders and help to form a uniform distribution. Specifically, the slow heating rate of 3 to 4 °C / min is conducive to promoting the formation of more crystal nuclei, thereby generating finer particles; within the temperature range of 300 to 400 °C, the formation of GDC can be effectively promoted while avoiding impurities or phase changes that may be introduced by high temperature; the holding time in the range of 4 to 6 hours can ensure sufficient holding time to allow the reaction to proceed fully and ensure that all precursors (Gd(NO3)3·6H2O and Ce(NO3)3·6H2O) are completely converted into the GDC phase. Incomplete reactions may result in unreacted substances remaining in the product, affecting the purity and performance of the powder. In addition, a longer holding time helps the uniform growth of particles and avoids the uneven particle size caused by rapid cooling, thereby obtaining a more uniform particle size distribution. Furthermore, the particle size of the GDC nanopowder is 7 to 15 nm, and the powder particles within this size range also help to improve the density of the subsequent cold sintering step.
[0048] In a specific embodiment of the present invention, the GDC nanopowder is Ce 0.8 G 0.2 O 1.9 Nano powder, the steps of preparing GDC nano powder include: according to Ce 0.8 G 0.2 O 1.9 Gd(NO3)3·6H2O and Ce(NO3)3·6H2O were weighed chemically and then mixed and ground.
[0049] In a specific embodiment of the present invention, the molar ratio of Gd(NO3)3·6H2O and Ce(NO3)3·6H2O in the sintering aid is 1:4, and the mass of the sintering aid accounts for 5wt% to 20wt% of the total mass of the sintering aid and the nanopowder. The inventors have found through experiments that the molar ratio and the amount of addition can not only help the sintering aid to properly play the role of a liquid aid in the early stage of cold sintering, effectively promote the close arrangement of GDC nanoparticles under pressure, but also properly fill the pores in GDC without causing negative effects. When the sintering aid is excessive, the sintering aid will be squeezed out during the cold sintering pressurization, affecting the cold sintering process, and the sintering aid flows to the outside of the matrix, may adhere to the outer surface of the electrolyte matrix, and be sintered and formed in the second half of the cold sintering process, and the desired electrolyte matrix with a GDC barrier layer cannot be obtained; when the sintering aid is small, the sintering aid cannot fully play its function, and cannot effectively improve the density after the subsequent pyrolysis growth into GDC.
[0050] In a specific embodiment of the present invention, the mass ratio of the printing powder to the binder is 0.8-1.5. Too little or too much binder will cause the initial slurry to be too thin or too viscous and cannot be printed on the substrate. Specifically, the binder is prepared by mixing ethyl cellulose and diethyl ethyl acetate in a mass ratio of 3%-10%.
[0051] In a specific embodiment of the present invention, in the cold sintering step after screen printing, the mesh number of the screen is 200-300 meshes, 1≤n≤5, the total thickness of n layers is 5-20μm, and the drying temperature is 100-150°C. In this process, the printing paste prepared by GDC nanopowder and sintering aid is brushed onto the electrolyte matrix, and the mesh number of the screen, the number of printing layers (i.e., the printing thickness) and the drying temperature are controlled to prepare for the subsequent cold sintering. In particular, the mesh number of the screen can further ensure the fineness and uniformity of the nanoparticles of the barrier layer, which helps to achieve more consistent sintering behavior during the cold sintering process and reduce defects; within the thickness range of 5-20μm, the functional requirements of the barrier layer and the electrolyte can be achieved, the interface bonding strength between the barrier layer and the electrolyte matrix and the performance stability of the barrier layer can be ensured; and the drying temperature is controlled at 100-150°C, which can further ensure the structural integrity of the barrier layer.
[0052] In a specific embodiment of the present invention, the cold sintering temperature of the cold sintering treatment is 250-350°C, specifically, the heating rate is 5-20°C / min, more specifically, the heating rate is 10°C / min. By controlling the heating rate, the sintering aid can be fully promoted to rearrange the particles when it is liquid, and it can be fully grown in the subsequent pyrolysis in-situ generation of GDC particles, thereby more effectively improving the density. The pressure of the cold sintering process is 150-400MPa, and the holding time is 0.5-5 hours. The cold sintering temperature range is set at 250-350°C, which is sufficient to promote the densification process of GDC nanopowders without causing excessive grain growth. Moreover, as mentioned above, in the first half of the cold sintering process, the sintering temperature is relatively low, below 300°C. During this process, the sintering aids Gd(NO3)3·6H2O and Ce(NO3)3·6H2O begin to become liquid, playing a lubricating role in the sintering process and promoting ion rearrangement. As the temperature rises further, the sintering aids begin to pyrolyze, and then GDC particles are generated in situ to fill the pores and increase the density. In addition, applying a pressure of 150 to 400 MPa during cold sintering can effectively promote the densification of the material and improve the ion conductivity. The 0.5 to 5 hour insulation time ensures the completeness of the chemical reaction and densification process. Sufficient insulation time allows the stress inside the material to be redistributed and reduces structural defects.
[0053] In a specific embodiment of the present invention, in the cold sintering step after screen printing, the electrolyte matrix printed with the printing slurry is placed in a mold, and a mica sheet is used as a gasket for cold sintering, followed by demoulding. Cold sintering is used to prepare thin layer materials, and demoulding is a key technology that affects the integrity of the sample. Ordinary stainless steel and carbon paper are used as gaskets for cold sintered samples, which are easy to adhere to the thinner GDC barrier layer, making it difficult to prepare a complete barrier layer. Mica sheets are used as gaskets. Mica sheets are resistant to high temperatures and have a smooth and stable surface. They are not easy to adhere to the GDC barrier layer, and the sample can be completely removed to obtain a complete GDC barrier layer material.
[0054] In a specific embodiment of the present invention, in the annealing step, the annealing temperature is 900-1300°C, the heating rate is 1-10°C / min, and the holding time is 1-5 hours. In the aforementioned steps, the density is effectively improved by controlling the pyrolysis reaction to obtain small-size powder particles, selecting and adding sintering aids, and rationally regulating the cold sintering process. Therefore, in the annealing step, the annealing temperature can be reduced to 900-1300°C, reducing energy consumption and reducing production costs. At the same time, the control of annealing temperature, heating rate, and holding time can further ensure that a GDC barrier layer with a higher density is obtained, improve interface performance, and help to further improve battery performance.
[0055] In a specific embodiment of the present invention, the electrolyte matrix is a YSZ electrolyte matrix.
[0056] The second aspect of the present invention discloses an electrolyte for a solid oxide battery, wherein the electrolyte comprises a GDC barrier layer, and the GDC barrier layer is prepared by the above method.
[0057] The second aspect of the present invention discloses a solid oxide battery, comprising an electrolyte matrix and a GDC barrier layer, wherein the GDC barrier layer is prepared by the above method.
[0058] Since the density of the barrier layer and the interface performance between the barrier layer and the electrolyte matrix are improved, the performance of the electrolyte and the battery are improved, and the life of the battery is also extended.
[0059] The following will be described in conjunction with more specific implementation methods.
[0060] Examples 1-4 are prepared GDC barrier layers attached to a YSZ electrolyte substrate, and the specific preparation method is as follows:
[0061] Preparation of Example 1:
[0062] Preparation of GDC nanopowder: Gd(NO3)3·6H2O and Ce(NO3)3·6H2O were prepared according to Ce 0.8 G 0.2 O 1.9 The weight of the mixture was weighed according to the chemical formula ratio, and then fully ground in a mortar. After being mixed evenly, the mixture was placed in a muffle furnace for heating to perform pyrolysis reaction. The heating rate was 3°C / min, the pyrolysis temperature was 300°C, and the insulation time was 5h. After the insulation was completed, the GDC nanopowder was prepared by cooling the furnace.
[0063] Preparation of printing powder: using the GDC nanopowder prepared in the first step as a raw material, a mixture of Gd(NO3)3·6H2O and Ce(NO3)3·6H2O as a sintering aid, the molar ratio of Gd(NO3)3·6H2O to Ce(NO3)3·6H2O being 1:4, weighing the GDC nanopowder and the sintering aid at a mass ratio of 1:0.15 and fully grinding and mixing to obtain a printing powder;
[0064] Preparation of printing paste: mixing printing powder and binder at a mass ratio of 1:0.9, and preparing screen printing paste after vacuum degassing and three-roller ball milling, wherein the binder is ethyl cellulose and diethyl ethyl acetate at a mass ratio of 7%;
[0065] After screen printing, cold sintering treatment is performed: 2 layers of printing slurry are printed on the YSZ electrolyte substrate using a 300 mesh screen, and the total thickness of the 2 layers is 10 μm. Then it is dried at 120°C and placed in a mold for cold sintering treatment. The gasket is a mica sheet, the cold sintering temperature is 350°C, the pressure is 150 MPa, the insulation time is 0.5 h, and the initial green body is obtained by demolding after cooling.
[0066] Annealing treatment: the initial green body is annealed to obtain a GDC barrier layer attached to the YSZ electrolyte matrix. Specifically, the heating rate is 2°C / min, the annealing temperature is 1300°C, and the holding time is 2 hours.
[0067] Preparation of Example 2:
[0068] The only difference between Example 2 and Example 1 is that the pyrolysis temperature is 350°C and the annealing temperature is 1400°C.
[0069] Preparation of Example 3:
[0070] The only difference between Example 3 and Example 1 is that the added amount of the sintering aid is 5 wt % and the annealing temperature is 1000° C.
[0071] Preparation of Example 4:
[0072] The only difference between Example 4 and Example 1 is that the added amount of the sintering aid is 10 wt %, the thickness of the screen printing is 20 μm, and the mass ratio of the GDC nano powder to the binder in the printing paste is 1:1.5.
[0073] Comparative Example 1 is a GDC barrier layer attached to a YSZ electrolyte substrate prepared by a conventional sintering method, and the specific preparation method is as follows:
[0074] Commercial GDC powder and a binder are mixed in a mass ratio of 1:0.9, wherein the binder is ethyl cellulose and diethyl ethyl acetate in a mass ratio of 7%. After vacuum degassing and three-roller ball milling, a screen printing slurry is prepared. The printing slurry is printed on a YSZ electrolyte substrate in two layers with a thickness of 10 μm using a 300-mesh screen. The printed slurry is then dried at 120°C. The dried sample is annealed to obtain a GDC barrier layer attached to the YSZ electrolyte substrate. Specifically, the heating rate is 2°C / min, the annealing temperature is 1300°C, and the insulation time is 2 hours.
[0075] The GDC nanopowder prepared in Example 1 was sampled and photographed by TEM. Figure 1 As shown in FIG. 1 , the particle size of the nano powder is about 7-15 nm. The GDC barrier layer sample attached to the YSZ electrolyte matrix prepared in Example 1 was processed to obtain a sample suitable for XRD analysis, as shown in FIG. Figure 2 As shown, the diffraction peaks of GDC and YSZ are obvious in the XRD spectrum, indicating that it is a two-phase material and no other impurity phase is generated.
[0076] Examples 1-4 and Comparative Example 1 were cut to obtain cross-sectional samples suitable for SEM photography. Since the barrier layer is very thin, the density is difficult to quantify. Therefore, the SEM image is observed by naked eyes to evaluate the density. Figure 3 As shown in the figure, it can be seen that the thickness is about 10 μm, and the degree of densification is high. The dense barrier layer can effectively prevent the generation of impurities and improve the performance of the fuel cell. Figure 4 As shown, compared with Example 1, the density of Comparative Example 1 is not high and there are more pores. The physical phases of Example 2 are still GDC and YSZ phases, no impurity phases are generated, and the density of the sample is high. The density of Examples 3 and 4 is relatively lower than that of Example 1, but better than Comparative Example 1, and no impurity phases are generated.
[0077] Although the present invention has been illustrated and described with reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.
Claims
1. A method for preparing a GDC barrier layer of a solid oxide fuel cell, characterized in that: The following steps are involved: Preparation of GDC nanopowder: Gd(NO3)3·6H2O and Ce(NO3)3·6H2O were mixed and ground, and then GDC nanopowder was prepared by pyrolysis reaction; Preparation of printing powder: GDC nano powder and sintering aid are mixed and ground to obtain printing powder, wherein the sintering aid comprises Gd(NO3)3·6H2O and Ce(NO3)3·6H2O, the molar ratio of Gd(NO3)3·6H2O to Ce(NO3)3·6H2O in the sintering aid is 1:4, and the mass of the sintering aid accounts for 5wt% to 20wt% of the total mass of the sintering aid and the GDC nano powder; Preparing printing paste: mixing printing powder with a binder to prepare printing paste; Cold sintering treatment is performed after screen printing: the printing paste is printed on the electrolyte matrix using a screen plate and dried, and then cold sintering treatment is performed to obtain an initial green body; Annealing treatment: The initial green body is annealed to obtain a GDC barrier layer attached to the electrolyte matrix.
2. The preparation method according to claim 1, characterized in that In the step of preparing GDC nanopowder, a pyrolysis reaction is carried out in a muffle furnace to prepare GDC nanopowder. The heating rate of the pyrolysis reaction is 3-4°C / min, the pyrolysis temperature is 300-400°C, the insulation time is 4-6 hours, and the powder is cooled with the furnace after the insulation is completed.
3. The preparation method according to claim 2, characterized in that: The GDC nano powder is Ce 0.8 G 0.2 O 1.9 Nano powder, the steps of preparing GDC nano powder include: according to Ce 0.8 G 0.2 O 1.9 Chemical formula Weigh Gd(NO3)3·6H2O and Ce(NO3)3·6H2O, mix and grind.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the printing powder to the binder is 0.8-1.5, and the binder is prepared by mixing ethyl cellulose and diethyl ethyl acetate in a mass ratio of 3%-10%.
5. The preparation method according to claim 1, characterized in that: In the cold sintering step after screen printing, the mesh number of the screen is 200-300 meshes, n layers are printed on the electrolyte matrix, wherein 1≤n≤5, the total thickness of the n layers is 5-20 μm, and the drying temperature is 100-150° C.
6. The preparation method according to claim 1, characterized in that: The cold sintering temperature of the cold sintering treatment is 250-350° C., the heating rate is 5-20° C. / min, the pressure of the cold sintering process is 150-400 MPa, and the heat preservation time is 0.5-5 hours.
7. The preparation method according to claim 1, characterized in that: In the step of cold sintering after screen printing, the electrolyte substrate printed with the printing paste is placed in a mold, a mica sheet is used as a gasket, and cold sintering is performed, followed by demoulding.
8. The preparation method according to claim 1, characterized in that: In the annealing step, the annealing temperature is 900-1300° C., the heating rate is 1-10° C. / min, and the heat preservation time is 1-5 hours.
9. The preparation method according to claim 2, characterized in that: The particle size of the GDC nano powder is 7 to 15 nm.
10. The preparation method according to claim 1, characterized in that: The electrolyte matrix is a YSZ electrolyte matrix.
11. An electrolyte for a solid oxide battery, characterized in that: The electrolyte comprises an electrolyte matrix and a GDC barrier layer attached to the electrolyte matrix, wherein the GDC barrier layer is prepared by the method according to any one of claims 1 to 10.
12. A solid oxide battery, characterized in that: The solid oxide battery comprises the electrolyte of a solid oxide battery as claimed in claim 11.
Citation Information
Cited By
Solid oxide fuel cell barrier layer material and preparation method thereof
CN120473520A
Preparation method of compact barrier layer for solid oxide battery
CN121076174A
METHOD FOR PRODUCING THIN-FILM ELECTROLYTE BASED ON Ce1-XGdXO2 ON SURFACE OF NiO / GDC ANODE BLANK
RU2859963C1
